Mobilising SDG 12: co-creating sustainability through brands. Issue 2 (2020) - Palakshappa, Nitha; Dodds, Sarah
Abstract : Purpose: This research extends understanding of the role brand co-creation plays in encouraging ethical consumption. The paper addresses sustainable development goal 12 (SDG 12): ensure sustainable consumption and production patterns, exploring how brand co-creation can be employed to advance this development goal. Design/methodology/approach: The Customer Brand Co-creation Model is used within an embedded case design to understand the role of the brand and the consumer in promoting sustainable consumption within the fashion industry. Findings: Initial insights suggest marketing has much to offer sustainability through the use of the brand. An extended brand co-creation framework highlights the importance of embedding sustainability and viewing the consumer as central to mobilising SDG12. Practical implications: An important concern is to ensure sustainability is embedded within the activities and strategy of the organisation and viewed as integral rather than peripheral. Originality/value: The paper examines aspects crucial to co-creation of "sustainability" through a focus on both the consumer and the brand. Case narratives provide a strong foundation to consider the Customer Brand Co-creation Model and implications of this framework for managerial practice. This study extends the model to encompass the umbrella of "sustainability" and the firm's perspective.